Improved Sliding Mode Control for Performance Enhancement of PMD Battery Charger Using Fuzzy Logic Control - Gyuri Kim; Yeongsu Bak (IEEE Access)
This paper presents an improved sliding mode control (SMC) for performance enhancement of personal mobility device (PMD) battery charger using fuzzy logic control. The PMD industry has recently been activated to reduce environmental pollution and accordingly, research on PMD battery chargers is being actively conducted. Typically, proportional-integral (PI) control or SMC methods are used to control the output voltage and inductor current of PMD battery charger. However, increasing the gain of PI controllers and SMC method to improve performance results in overshoot in output voltage and ripple in inductor current due to chattering phenomena. Therefore, to overcome the disadvantage, this paper presents improved sliding mode control for performance enhancement of PMD battery charger using fuzzy logic control (FLC). The proposed control method determines the gain used in the SMC by using FLC, and determines the gain of the controller through the membership function and the output intensity, thereby reducing ripple and improving responsiveness. The validity of the proposed control method is verified by the simulation and experimental results.